2015
DOI: 10.5902/1980509820582
|View full text |Cite
|
Sign up to set email alerts
|

FERTILIZANTE DE LIBERAÇÃO LENTA NO DESENVOLVIMENTO DE MUDAS DE <i> Anadenanthera peregrina </i> (L.) Speg. (ANGICO-VERMELHO) E <i> Schinus terebinthifolius </i> Raddi (AROEIRA-VERMELHA)

Abstract: RESUMOCom o objetivo de avaliar o desenvolvimento de duas espécies arbóreas nativas -Anadenanthera peregrina (angico-vermelho) e Schinus terebinthifolius (aroeira-vermelha) -submetidas a doses de fertilizante de liberação lenta na formulação 13-06-16, conduziu-se um experimento em viveiro utilizando uma mistura de matérias-primas com composto orgânico, vermiculita e Plantmax® para compor substrato base. O experimento foi conduzido no delineamento experimental inteiramente casualizado com seis tratamentos em qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 2 publications
3
14
0
9
Order By: Relevance
“…This trend was also reported by Rossa et al (2015), who verified that CRF application results in significant growth gains for cohoba tree (Anadenanthera peregrina) and Brazilian peppertree seedlings (Schinus terebinthifolius), with the best doses for cohoba tree between 5.54 and 6.68 kg m -3 and for Brazilian peppertree between 8.38 and 14.42 kg m -3 . Dutra et al (2016) concluded that yellow poinciana (Peltophorum dubium) seedlings responded to CRF, showing best growth and quality standard at doses between 5.4 and 8.2 g dm -3 .…”
Section: Variablesupporting
confidence: 80%
“…This trend was also reported by Rossa et al (2015), who verified that CRF application results in significant growth gains for cohoba tree (Anadenanthera peregrina) and Brazilian peppertree seedlings (Schinus terebinthifolius), with the best doses for cohoba tree between 5.54 and 6.68 kg m -3 and for Brazilian peppertree between 8.38 and 14.42 kg m -3 . Dutra et al (2016) concluded that yellow poinciana (Peltophorum dubium) seedlings responded to CRF, showing best growth and quality standard at doses between 5.4 and 8.2 g dm -3 .…”
Section: Variablesupporting
confidence: 80%
“…Dutra et al (2016) did not detect an effect of slow release fertilizers on the DQI variable in Cassia-fistula, L. seedlings. Rossa et al (2014), Melo et al (2015) and Rossa et al (2015) detected positive effects of slow release fertilizer doses on Gallesia integrifolia, yellow passion fruit, red angico and red passion fruit seedlings, respectively. Cruz et al (2011) affirm that the DQI, as it expresses the quality of the seedlings, considers the robustness and balance of the biomass distribution in the seedling.…”
Section: /10mentioning
confidence: 99%
“…The use of controlled-release fertilizers is a nutritional contribution technology for forest species (Rossa et al, 2015a). These fertilizers include soluble compounds in their interior (NPK and some micronutrients) surrounded by a semipermeable membrane that, depending on the temperature and humidity of the substrate, dilates and contracts, which causes the release of nutrients to be controlled and made available gradually, thereby maintaining constant levels of the essential elements for the seedlings throughout the growth period (Bennett, 1996;José et al, 2009).…”
Section: Introductionmentioning
confidence: 99%